2012
DOI: 10.1007/s11192-012-0929-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparing journals from different fields of science and social science through a JCR subject categories normalized impact factor

Abstract: The journal Impact Factor (IF) is not comparable among fields of Science and Social Science because of systematic differences in publication and citation behaviour across disciplines. In this work, a decomposing of the field aggregate impact factor into five normally distributed variables is presented. Considering these factors, a Principal Component Analysis is employed to find the sources of the variance in the JCR subject categories of Science and Social Science. Although publication and citation behaviour … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 30 publications
0
29
0
1
Order By: Relevance
“…The IF of the journal, a publisher's prestige, their inclusion in abstracting and indexing databases, and an online submission with tracking facility are statistically significantly more important to medical authors than to scholars in the social sciences (see Figure 2). Many studies have claimed that the IF's influence can differ widely across disciplines (Dorta-Gonzalez & Dorta-González, 2013;Scully & Lodge, 2005;Seglen, 1997). Althouse et al (2009) and Amin and Mabe (2004) have independently identified major reasons for higher IF values in medicine than in the social sciences.…”
Section: Mean and Median Values For Scholars In Both Domains Showmentioning
confidence: 99%
“…The IF of the journal, a publisher's prestige, their inclusion in abstracting and indexing databases, and an online submission with tracking facility are statistically significantly more important to medical authors than to scholars in the social sciences (see Figure 2). Many studies have claimed that the IF's influence can differ widely across disciplines (Dorta-Gonzalez & Dorta-González, 2013;Scully & Lodge, 2005;Seglen, 1997). Althouse et al (2009) and Amin and Mabe (2004) have independently identified major reasons for higher IF values in medicine than in the social sciences.…”
Section: Mean and Median Values For Scholars In Both Domains Showmentioning
confidence: 99%
“…This formulation allows us to easily obtain the citation potential of the JCR database, which is 2.822 in year 2011 (Dorta-González & Dorta-González, 2013a). It also allows us to calculate, in a similar way, the citation potential in any set of journals (as discussed below).…”
Section: The Citation Potential Of a Databasementioning
confidence: 99%
“…Garfield (1979) proposes the term 'citation potential' for systematic differences among fields of science, based on the average number of references. For example, in the biomedical fields long reference lists with more than fifty items are common, but in mathematics short lists with less than twenty references are the standard (Dorta-González & Dorta-González, 2013a). These differences are a consequence of the citation cultures and can produce significant differences in the JIF, since the probability of being cited is affected.…”
Section: Introductionmentioning
confidence: 99%
“…However Brody agreed that impact factor is imperfect but not yet replaceable, because substantial alternatives has no clear improvements over IF as a single measure (Brody, 2013). In response to critics, Thomson Reuters supple-mented more indicators: Five year impact factor, Eigenfactor score, Article Influence Score in the online version of JCR (Dorta-Gonzalez and Dorta-Gonzalez, 2012). Also there has been approach to apply rank normalization to solve Vanclay's dilemma with impact factor (Pudovkin and Garfield, 2012).…”
Section: Introductionmentioning
confidence: 99%